EMOTIONAL INTELLIGENCE: A GUIDE TO CRITICAL INFORMATION LITERACY IN THE DIGITAL AGE - Rahma, Nadhifia Shabrina Nur; Inriani, Sefania Wenny Eka; Margono, Hendro (Pustakaloka, 2025)
The digital age has created an overwhelming amount of information, making it very important to know how to use it. This study seeks to investigate the influence of emotional intelligence on the enhancement of these skills. This study employed a Systematic Literature Review (SLR) methodology to examine four scientific articles published from 2020 to 2024, sourced from the Google Scholar database. The main findings indicate that individuals with high emotional intelligence tend to be more capable of managing emotions when faced with contradictory information, are more open to diverse perspectives, and show improvements in digital literacy and learning outcomes. These findings indicate that cultivating emotional intelligence may serve as an effective strategy for improving critical information literacy. This analysis leads to the conclusion that emotional intelligence is crucial for promoting logical decision-making, preventing the dissemination of false information, and successfully navigating the complexity of digital information.